Association of vitamin D with depression prevalence in U.S. adults: a cross-sectional analysis from NHANES 2021 to 2023 - Huang, Chuan; Xu, Jiaojiao; Qiu, Hai; Yue, Yuchuan (Frontiers in Nutrition, 2025)
BackgroundVitamin D plays a wide array of physiological functions and is believed to influence various aspects of mental health. This cross-sectional study investigates the associations between serum levels of vitamin D isoforms—vitamin D2 (ergocalciferol) and D3 (cholecalciferol)—and the presence of depressive symptoms among U.S. adults.MethodsAn analysis was conducted on data collected from 3,863 adults in the 2021–2023 National Health and Nutrition Examination Survey (NHANES). Serum vitamin D levels, represented by the combined concentrations of 25-hydroxyvitamin D2 and D3, were quantified. Depressive symptoms were evaluated through the Patient Health Questionnaire-9 (PHQ-9), where scores reaching 10 or above suggested their presence. Multivariable logistic regression models were utilized to investigate the links between vitamin D concentrations and depression, taking into account demographic and health-related factors.ResultsElevated levels of vitamin D in the serum were linked to reduced likelihood of exhibiting depressive symptoms. Specific findings indicated that increased levels of vitamin D3 correlated with a decrease in depressive symptoms, while elevated levels of vitamin D2 were linked to an increase in such symptoms. Even after accounting for potential confounding factors like age, gender, ethnicity, and socioeconomic status, these relationships remained evident.ConclusionThe study identifies distinct associations of different vitamin D isoforms with the presence of depressive symptoms, suggesting differing roles of vitamin D2 and D3 in mental health. These findings highlight the need for specific consideration of vitamin D isoforms in dietary recommendations and public health strategies aimed at mental health. Additional studies are required to clarify the underlying mechanisms responsible for these associations.